Management accounting practice in climate change era: Lesson learned from sensitive industries - Kawulur, Hisky Ryan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study examines the implementation of carbon management accounting practices within six climate-sensitive industries in Indonesia.Design/Methodology/Approach: Employing content analysis and K-means clustering by sector and year, this research investigates 198 firm-years covering the period from 2016 to 2022.Research findings: The findings reveal three distinct clusters that illustrate variations in corporate behavior concerning the adoption of carbon management accounting practices. These discrepancies are attributable to divergent corporate perceptions of risks, opportunities, and stakeholder expectations related to climate change. Furthermore, the study delineates three phases that reflect the progression of carbon management accounting in Indonesia.Theoretical contribution/ Originality: This research offers valuable insights for effectively addressing the risks and opportunities associated with climate change. This research brings a fresh perspective by examining how companies adapt and transform their management accounting practices to address the risks posed by climate change. Practitioner/Policy implication: The findings indicate that as climate change regulations become clearer, including sanctions and incentives, companies become more proactive in implementing carbon management accounting. Conversely, when environmental regulations lack clarity or are less stringent, companies tend to deviate, prioritizing economic performance over environmental performance.